EARLY WEANING AND THE INFLUENCE ON THE APPEARANCE OF HARMFUL ORAL HABITS:: LITERATURE REVIEW - Daiane Souto Luz da Silva , Anne; Beatriz de Siqueira Melo Galindo, Paula; Ciane Silveira Cirino de Britto Galvão, Thaís; Machado Lima, Brunela (Health and Society, 2021)
Breastfeeding is essential for the child’s physical and psychological development, contributing to the mother-child relationship, reducing the risks of infections and malnutrition. The present work aims to verify the relationship between early weaning and the appearance of harmful oral habits, through a review of narrative literature, a search was performed in the Bireme, VHL, Pubmed/MEDILINE data bases and virtual library platform my library, in the Portuguese and English languages of the last 16 years. Therefore, it is observerd that there is a direct interconnection between these two aspects, which highlights the importance of health actions aimed at pregnant women and women who have recently given birth.